Semi-individualised Chinese medicine treatment as an adjuvant management for diabetic nephropathy: a pilot add-on, randomised, controlled, multicentre, open-label pragmatic clinical trial. Issue 8 (5th August 2016) - Chan, Kam Wa; Ip, Tai Pang; Kwong, Alfred Siu Kei; Lui, Sing Leung; Chan, Gary Chi Wang; Cowling, Benjamin John; Yiu, Wai Han; Wong, Dickson Wai Leong; Liu, Yang; Feng, Yibin; Tan, Kathryn Choon Beng; Chan, Loretta Yuk Yee; et al.
Abstract : Introduction: Diabetes mellitus and diabetic nephropathy (DN) are prevalent and costly to manage. DN is the leading cause of end-stage kidney disease. Conventional therapy blocking the renin–angiotensin system has only achieved limited effect in preserving renal function. Recent observational data show that the use of Chinese medicine (CM), a major form of traditional medicine used extensively in Asia, could reduce the risk of end-stage kidney disease. However, existing clinical practice guidelines are weakly evidence-based and the effect of CM remains unclear. This trial explores the effect of an existing integrative Chinese–Western medicine protocol for the management of DN. Objective: To optimise parameters and assess the feasibility for a subsequent phase III randomised controlled trial through preliminary evaluation on the effect of an adjuvant semi-individualised CM treatment protocol on patients with type 2 diabetes with stages 2–3 chronic kidney disease and macroalbuminuria. Methods and analysis: This is an assessor-blind, add-on, randomised, controlled, parallel, multicentre, open-label pilot pragmatic clinical trial. 148 patients diagnosed with DN will be recruited and randomised 1:1 to a 48-week additional semi-individualised CM treatment programme or standard medical care. Primary end points are the changes in estimated glomerular filtration rate and spot urine albumin-to-creatinine ratio between baseline and treatment end point. Secondary end points include fasting blood glucose, glycated haemoglobin, brain natriuretic peptide, fasting insulin, C peptide, fibroblast growth factor 23, urinary monocyte chemotactic protein-1, cystatin C, nephrin, transforming growth factor-β1 and vascular endothelial growth factor. Adverse events are monitored through self-completed questionnaire and clinical visits. Outcomes will be analysed by regression models. Enrolment started in July 2015. Ethics and registration: This protocol is approved by the Institutional Review Board of the University of Hong Kong/Hospital Authority Hong Kong West Cluster (reference number UW 14-301). Trial registration number: NCT02488252.